(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2024)
The study considers the features of nature management of one of the large mountain pastures of Ile Alatau in the Asy River valley (Northern Tien Shan). Located on a mountain plateau at an altitude of 2200-2800 m, the pasture is characterized by landscape and biological diversity, highly productive plant communities. The state of plant associations of the Asy valley was studied in the second half of the 1990s, when natural pastures were practically not used due to socio-economic collisions, which ensured pronounced demutational and regenerative processes of grass phytocenoses. These restoration processes took place against the background of unfavorable climatic changes: less precipitation and higher air temperature in the warm period. Subsequent field work dates back to the period 2012-2020, when the ecosystems of the Assy River valley experienced a powerful anthropogenic impact in the form of overgrazing, press of tourists and poachers. At the same time, the vast majority of livestock breeders do not consider the obvious degradation of pastures and do everything possible to increase the number of livestock, violating the principles of sustainable use of pastures. In these conditions it is completely unrealistic to organize works on improvement, phytoremediation of fodder vegetation. Undoubtedly, it is necessary to carefully organize the use of highly productive alpine pastures and strict control over the number of grazing livestock. Much awareness raising and organization of a harmonious balance between economic and ecological components is necessary. Recommendations are given on the use of different systems for monitoring, restoration and sustainable use of pasture ecosystems in the region. Keywords: ecosystem services, mountain pastures, Ile Alatau, overgrazing, degradation and restoration of plant resources, monitoring and phytoremediation, sustainable pasture management